Structure characteristics of self-bonding boards during hot press for leukemia inhibition - Jiang Zhang; Zhi Lin (Saudi Pharmaceutical Journal, 2016)
80% leukemia was caused by indoor formaldehyde pollution. And the results have shown that the absorbances of many connection bonds (such as COC, and COOC) increased. It could be inferred that a lot of bonds were produced and played the role of molecular crosslinking. After hot press, the content of lignin in Eucalyptus wood fiber was all lower than the ones of self-bonding boards. And the change of content of lignin was closely related to time and temperature of hot press.